Chemical, biochemical and microbiological properties of a brominated nitrovinylfuran with broad-spectrum antibacterial activity - Scholz, Therese; Heyl, Carina; Zimmermann, Stefan; Klein, Christian D. (Bioorganic & medicinal chemistry, 2013)
A di-bromo substituted nitrovinylfuran with reported broad-spectrum antibacterial activity was found to be a potent inhibitor of MurA, a key enzyme in peptidoglycan biosynthesis. Further characterization of the compound was carried out to assess its reactivity towards thiol nucleophiles, its stability and degradation under aqueous conditions, inhibitory potential at other enzymes, and antibacterial and cytotoxic activity. Our results indicate that the nitrovinylfuran derivative is reactive towards cysteine residues in proteins, as demonstrated by the irreversible inhibition of MurA and bacterial methionine aminopeptidase. Experiments with proteins and model thiols indicate that the compound forms covalent adducts with SH groups and induces intermolecular disulfide bonds, with the intermediate formation of a monobromide derivative. The parent molecule as well as most of its breakdown products are potent antibiotics with MIC values below 4μg/mL and are active against multiresistant strains such as methicillin-resistant Staphylococcus aureus (MRSA). Further development of the bromonitrovinyl scaffold towards antibiotics with clinical relevance, however, requires optimization of the antibiotic-cytotoxic selectivity profile.